1994
DOI: 10.1111/j.1432-1033.1994.tb18897.x
|View full text |Cite
|
Sign up to set email alerts
|

The purification of early‐pregnancy factor to homogeneity from human platelets and identification as chaperonin 10

Abstract: Early‐pregnancy factor (EPF), first discovered in the early stages of gestation, is associated with and necessary for cell proliferation in a wide variety of biological situations. Like many other growth factors, EPF is present in platelets, and, by titration studies with a neutralising anti‐EPF monoclonal antibody, platelets were identified as an extremely rich source of this growth factor. EPF has been purified from clinically outdated human platelets by heat extraction, ion‐exchange and affinity chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 46 publications
(48 reference statements)
0
94
1
1
Order By: Relevance
“…In light of recent findings suggesting that cpnl0 are multifunctional molecules one may also speculate that N-terminal acetylation could be relevant in functions other than assisting cpn60 in protein folding. Comparative studies of natural and recombinant cpnl0 in those biological systems that have been studied so far only with the natural form [13] may help clarify this issue. The availability of recombinant human cpnl0 will facilitate to address these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of recent findings suggesting that cpnl0 are multifunctional molecules one may also speculate that N-terminal acetylation could be relevant in functions other than assisting cpn60 in protein folding. Comparative studies of natural and recombinant cpnl0 in those biological systems that have been studied so far only with the natural form [13] may help clarify this issue. The availability of recombinant human cpnl0 will facilitate to address these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that human cpnl0 is identical to the early pregnancy factor (EPF) [13]. EPF has been known for long time to be involved in a number of physiological processes which are apparently unrelated to the role of cpnl0 in protein folding, but its characterisation has been elusive due to the difficulties encountered in its purification [13]. Here, we report the high-level expression of human cpnl0 in Escherichia coli.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some 30 years ago, 1 year before the discovery of the first molecular chaperone, a circulating immunosuppressive activity, termed early pregnancy factor (EPF), was discovered (Morton et al 1977). This turned out to be the molecular chaperone, chaperonin (Cpn)/heat shock protein (Hsp)10, a mitochondrial protein (Cavanagh and Morton 1994). Co-incidentally, both Hsp10 and the co-chaperone Hsp60 are now implicated as cell surface proteins essential for the capacitation of sperm, revealing a 'prior role' for these proteins in pregnancy (Walsh et al 2008).…”
Section: Secreted and Extracellular Molecular Chaperonesmentioning
confidence: 99%
“…Early pregnancy factor (EPF) is a molecule that is present, from soon after conception, in the sera of all pregnant mammals that have been tested (Morton et al 1992;Cavanagh 1996;Cavanagh 1997); EPF has immunomodulatory properties and growth factor properties (Morton et al 1982;Morton 1998). EPF was found to be homologous to cpn 10 (Cavanagh and Morton 1994).…”
Section: Introductionmentioning
confidence: 99%